Development and Evaluation of Jackfruit Bulb Slicer - HARITHA J KAVYA P.S SONIYA P.V; Dr. Sudheer K.P (Guide) (Tavanur 2017 Department of Food and Agricultural Processing Engineering)
Development and Evaluation of Jackfruit Bulb Slicer
Development and Evaluation of Jackfruit Bulb Slicer